STUDI MENGENAI PELAKSANAAN PERKAWINAN ANGKAP PADA MASYARAKAT GAYO DI KABUPATEN ACEH TENGAH DENGAN BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - DEVI ERAWATI (PREMISE LAW JURNAL, 2015)
Basically, the form of adat marriage in Gayonese is similar to that of the Indonesian people. In the Gayonese adat law, there is a specific marriage which is called ‘angkap’ marriage. This marriage usually consists of two types. First, a family that has the only daughter does not want her to move to her husband’s side. Secondly, a young man who has no family comes to a certain village; by conducting angkap marriage, he does not need to pay for dowry. This young man comes from the coastal area or from different ethnic group to Gayo; he has good manners and is willing to work. The angkap marriage has been ruled in the Gayonese adat law. Keywords: Implementation of Angkap Marriage, Controversy in Angkap   Marriage